A sociological analysis of perceptions of work motivation among young people and its relationship to unemployment: Field study in Ngoussa – Algeria - Massoudi, AbdelBasset; Al-Mahdi, Benaissa Muhammad (Journal of Humanities & Social Sciences, 2024)
This study came to find a sociological approach to the phenomenon of work and unemployment away from economic and political analysis. And his awareness of work or loss of awareness of them as he is not able to overcome unemployment, and from here he may lose confidence in himself and this leads him to suicide or to other social negatives related to unemployment, and the theoretical approach that we follow does not provide solutions to phenomena, but rather tries to give social models We define them with indicators and dimensions, and when they are determined, the same social model can occur, i.e. prediction of social facts, and a case study from one of the approaches or methodological tools appropriate to the theoretical approach that dealt with this topic, and we also search that work is one of the ways to achieve social arrangement and any kind of professions and jobs that The individual sees it or thinks that it achieves this arrangement for him in his social and urban field in which he interacts, or in other ways outside the field of work.